Vitamin D Time Profile Based on the Contribution of Non-Genetic and Genetic Factors in HIV-Infected Individuals of European Ancestry. Issue 3 (April 2015) - Guidi, Monia; Foletti, Giuseppe; McLaren, Paul; Cavassini, Matthias; Rauch, Andri; Tarr, Philip E; Lamy, Olivier; Panchaud, Alice; Telenti, Amalio; Csajka, Chantal; Rotger, Margalida; ,
Background: Vitamin D deficiency is prevalent in HIV-infected individuals and vitamin D supplementation is proposed according to standard care. This study aimed at characterizing the kinetics of 25(OH)D in a cohort of HIV-infected individuals of European ancestry to better define the influence of genetic and non-genetic factors on 25(OH)D levels. These data were used for the optimization of vitamin D supplementation in order to reach therapeutic targets. Methods: 1, 397 25(OH)D plasma levels and relevant clinical information were collected in 664 participants during medical routine follow-up visits. They were genotyped for 7 SNPs in 4 genes known to be associated with 25(OH)D levels. 25(OH)D concentrations were analysed using a population pharmacokinetic approach. The percentage of individuals with 25(OH)D concentrations within the recommended range of 20–40 ng/ml during 12 months of follow-up and several dosage regimens were evaluated by simulation. Results: A one-compartment model with linear absorption and elimination was used to describe 25(OH)D pharma-cokinetics, while integrating endogenous baseline plasma concentrations. Covariate analyses confirmed the effect of seasonality, body mass index, smoking habits, the analytical method, darunavir/ritonavir and the genetic variant in GC (rs2282679) on 25(OH)D concentrations. 11% of the inter-individual variability in 25(OH)D levels was explained by seasonality and other non-genetic covariates, and 1% by genetics. The optimal supplementation for severe vitamin D deficient patients was 300, 000 IU two times per year. Conclusions: This analysis allowed identifying factors associated with 25(OH)D plasma levels in HIV-infected individuals. Improvement of dosage regimen and timing of vitamin D supplementation is proposed based on those results.